Patient safety vulnerabilities for children with intellectual disability in hospital: a systematic review and narrative synthesis - Laurel Mimmo; Reema Harrison; Reece Hinchcliff (BMJ Publishing Group, 2018)
Purpose Adults and children with intellectual disability (ID) are vulnerable to preventable morbidity and mortality due to poor quality healthcare. While poor quality care has been commonly identified among children with ID, evidence of the patient safety outcomes for this group is lacking and therefore explored in this review.Data sources Systematic searches of six electronic bibliographic research databases were undertaken from January 2000 to October 2017, in addition to hand searching.Study selection Keywords, subject headings and MeSH terms relating to the experience of iatrogenic harm during hospitalisation for children with ID were used. Potentially relevant articles were screened against the eligibility criteria. Non-English language papers were excluded.Data extraction Data regarding: author(s), publication year, country, sample, health service setting, study design, primary focus and main findings related to measures of quality and safety performance were extracted.Results of data synthesis Sixteen studies met the inclusion criteria, with three themes emerging: the impact of the assumptions of healthcare workers (HCWs) about the child with ID on care quality and associated safety outcomes; reliance on parental presence during hospitalisation as a protective factor; and the need for HCWs to possess comprehensive understanding of the IDs experienced by children in their care, to scientifically deduce how hospitalisation may compromise their safety, care quality and treatment outcomes.Conclusion When HCWs understand and are responsive to children's individual needs and their ID, they are better placed to adjust care delivery processes to improve care quality and safety during hospitalisation for children with ID.